Fourteenth Annual Epworth League Convention at Lake Tahoe - Gordon, John C., 1887-1967 (photographer):::Creator::::::::::::
Members of the Epworth League Institute gather for a group photograph to commemorate their 14th annual meeting at Lake Tahoe. Two award banners and a Ukiah banner are visible.